Սիմեոն Երեւանցի կաթողիկոսի մի քարոզ - Հայրապետյան, Տ. Շահե Քահանա
In his unpublished two-volume Sermonary, the eminent 18th-century scholar and public figure Catholicos Simēon Erevants‘i (1763-1780) not only addresses religious and ecclesiastical matters but also references historical figures and events. In the second volume, containing his “External” or non-liturgical sermons, Simēon examines the factors that contributed to the downfall of Catholicos Sahak Ahagin. After the death of the previous Catholicos Alexander Buzandats‘i II (1753-1755), Sahak Keghets‘i, also known as “Ahagin,” (“the Tremendous”) was elected Catholicos. Simēon Erevants‘i voices his astonishment at the circumstances surrounding Sahak’s short tenure, questioning how someone could be elected as Catholicos without ever visiting Holy Etchmiadzin and retreat to a monastery, enjoying all the privileges of the Catholicos without engaging in any church-related matters. In 1759 Sahak’s removal from the Catholicosal throne was orchestrated, and bishop Yakob Shamakhets‘i was elected as his successor. In structuring the sermon—published here on the basis of Ms M2212, which is Simēon’s autograph— the Catholicos explains Sahak’s downfall and Yakob’s selection in terms of divine providence, referencing various episodes from the Bible, specifically the Old Testament. Видный мыслитель и общественный деятель, католикос Симеон Ереванци (1763-1780) в своей еще не изданной двухтомной «Книге проповедей», помимо церковных и религиозных тем, касается также исторических личностей и событий. Во втором томе небогослужебных проповедей он обратился к причинам, приведшим к падению католикоса Саака Кехеци (прозванного Ахагин – Великий). После смерти католикоса Александра II Бюзандаци (1753-1755) католикосом был избран Саак Кехеци. Автор выражает в проповеди недоумение по поводу того, что избранный католикос, даже не явившись в Св. Эчмиадзин, удалился в другую обитель и, пользуясь всеми правами Патриарха, не участвовал в руководстве церковью. В 1759 году Саак Кехеци был смещен с патриаршего престола, и на него возвели епископа Акоба Шамахеци. В изда- ваемой на основе автографа (рук. М2212) проповеди Симеон Ереванци пытается, обращаясь к примерам из Священного Писания, найти объяснение устранению с патриаршего престола Саака, а избрание Акоба преподносит как акт божественного промышления.
Keywords: Հրապարակումներ; Բանասիրություն